The role of cadres in utilizing integrated health post for toddler growth monitoring - Rania Purwanti; Kharisah Diniyah; Sholaikhah Sulistyoningtyas (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Integrated Health Post plays a crucial role in monitoring toddler growth as an effort to prevent nutritional problems and stunting in the community. The successful utilization of integrated health post is inseparable from the role of cadres as the spearhead of health services at the community level. Purpose: to describe the role of cadres in utilizing integrated health post for toddler growth monitoring. Method: a descriptive approach. Informants in this study consisted of midwives, integrated health post cadres, and mothers of toddlers selected using a purposive sampling technique. Data collection techniques were conducted through in-depth interviews and analyzed using thematic analysis. Results: The results showed that cadres have carried out their roles as servants, educators, motivators, companions, and community mobilizers. Cadres play an active role in toddler growth monitoring services, such as providing basic information regarding weighing results, reminding integrated health post schedules, and accompanying mothers of toddlers who experience growth problems or who rarely attend Integrated health post regularly. However, the role of cadres as educators has not been optimal due to limited educational materials, low cadre confidence, uneven training, and limited supporting facilities and infrastructure. Conclusion: The conclusion of this study indicates that capacity building for cadres is necessary through ongoing training and guidance from Community Health Center to ensure more effective, optimal, and sustainable monitoring of toddler growth in the community. Suggestion: It is recommended that Community Health Center provide continuous training, guidance, and adequate educational media and facilities to improve the capacity and confidence of cadres, especially in their role as educators, so that the implementation of Integrated health post services can be more optimal and sustainable